CONCIENCIA Y PERCEPCIÓN DE LAS MUELAS DEL JUICIO IMPACTADAS ENTRE ESTUDIANTES NO MÉDICOS EN SALEM: UN ESTUDIO TRANSVERSAL - Shravani, Inisha (2025)
Introduction: Impacted teeth may sometimes be asymptomatic but can also be associated with serious complications such as infections, cysts, or tumors. The common symptoms of impacted teeth include pain, swelling, and/or trismus (difficulty opening the mouth). Despite the potential for complications, public awareness of impacted teeth is low. Thus, this research aims to assess the awareness and consequences of impacted teeth among non-medical students. Materials and methods: This cross-sectional study was conducted among non-medical students in Salem, Tamil Nadu, India. A validated standard questionnaire was prepared in English with multiple-choice and yes or no questions. The survey was conducted online, and the validated questionnaire with an appended informed consent form was sent via Google Form application. The questionnaire consisted of questions about awareness of and the consequences of impacted teeth. The responses of the participants were recorded and analyzed for completeness. Incomplete forms were excluded from the study. Statistical analysis was performed using descriptive statistics, the Chi-square test for categorical variables, and the Mann–Whitney U test for group comparisons. Normality was assessed using the Kolmogorov–Smirnov and Shapiro–Wilk tests. Results: There were 207 (53.5%) males and 180 (46.5%) females. Of the study participants, 254 participants (65.6%) were unaware of impacted teeth, while 133 (34.4%) reported being aware. Even though females were fewer in number compared to males, they were more aware of the impacted wisdom teeth. Awareness was significantly higher among Arts and Science students compared to Engineering students (Chisquare test, p = 0.032). The study population was primarily between the ages of 17 and 25. The mean age was 20 years. Additionally, about 31% of participants were familiar with the time of eruption of wisdom teeth, indicating a moderate level of awareness among this group regarding a specific type of impacted tooth. This highlights the need for greater educational efforts to increase awareness about impacted teeth in the general population. Conclusion: The present study indicates that only 34.4% of the non-medical students were aware of wisdom teeth but were unaware of the complications of impacted teeth. Hence, a better awareness of impacted teeth and the associated problems should be created among non-medical students.